Optimizing Cultural Awareness Through Augmented Reality: An Analysis of Educational Media Needs in Indonesian Elementary Schools - Andayani; Khaerul Anam; Prabowo, Suryo (LJPI UI Bunga Bangsa Cirebon, 2025)
Indonesia’s rich cultural heritage faces challenges due to globalization and inadequate innovative educational methods. Objective: This study analyzes the need for Augmented Reality (AR)-based learning media to enhance cultural awareness in Indonesian elementary schools. Novelty: New insights into students’ perceptions and expectations towards the use of AR in local cultural learning. Methods: Using a quantitative, cross-sectional survey with purposive sampling (N=160, consisting of 150 students and 10 teachers), this study collected perceptions about traditional and AR-based cultural learning. Results: Findings from the study showed that 62% of students found traditional cultural learning uninteresting, while 87% expressed strong interest in AR due to its interactivity and ease of use. Conclusions: These findings underscore the potential of AR as a transformative tool for cultural education, urging policymakers and educators to adopt immersive technologies. Future studies could explore the long-term impact of AR on cultural retention.